RELT negatively regulates the early phase of the T‐cell response in mice. Issue 10 (2nd September 2018) - Choi, Beom K.; Kim, Seon‐Hee; Kim, Young H.; Lee, Don G.; Oh, Ho S.; Han, Chungyong; Kim, Yu I.; Jeon, Yoon; Lee, Ho; Kwon, Byoung S.
Abstract: RELT (tumor necrosis factor receptor superfamily member 19‐like, TNFRSF19L) is a TNFR superfamily member that is primarily expressed in immune cells and lymphoid tissues, but whose immunological function is not well‐defined. Here, we show that RELT is expressed by naive T cells and DCs, and their activation or maturation decreases RELT expression. Using RELT knockout (RELT −/− ) mice, we demonstrate that RELT deficiency selectively promotes the homeostatic proliferation of CD4 + T cells but not CD8 + T cells, and enhances anti‐tumor CD8 + T‐cell responses. We also demonstrate, using an adoptive transfer model in which RELT is knocked‐out in either the transferred transgenic CD8 + T cells or the recipient melanoma‐bearing mice, that RELT on multiple immune cells limits the hyper‐response of tumor‐specific CD8 + T cells. Hyper‐responsiveness of RELT‐deficient T cells was induced by promoting their proliferation. Taken together, our findings suggest that RELT acts as a negative regulator that controls the early phase of T‐cell activation probably by promoting T‐cell apoptosis. Abstract : New player in coinhibition of T cell: RELT‐mediated regulation of conventional and homeostatic proliferation of T cells. RELT expressing on resting T cells selectively inhibits homeostatic proliferation of CD4 + T cells, but not CD8 + T cells. In addition, RELT acts as a negative regulator that controls the early phase of T‐cell activation to avoid excessive T‐cell activation.